Multi-year tracking reveals extensive pelagic phase of juvenile loggerhead sea turtles in the North Pacific. Issue 1 (December 2016) - Briscoe, D.; Parker, D.; Bograd, S.; Hazen, E.; Scales, K.; Balazs, G.; Kurita, M.; Saito, T.; Okamoto, H.; Rice, M.; Polovina, J.; Crowder, L.
Abstract Background The juvenile stage of loggerhead sea turtles (Caretta caretta ) can last for decades. In the North Pacific Ocean, much is known about their seasonal movements in relation to pelagic habitat, yet understanding their multi-year, basin-scale movements has proven more difficult. Here, we categorize the large-scale movements of 231 turtles satellite tracked from 1997 to 2013 and explore the influence of biological and environmental drivers on basin-scale movement. Results Results show high residency of juvenile loggerheads within the Central North Pacific and a moderate influence of the Earth's magnetic field, but no real-time environmental driver to explain migratory behavior. Conclusions We suggest the Central North Pacific acts as important developmental foraging grounds for young juvenile loggerhead sea turtles, rather than just a migratory corridor. We propose several hypotheses that may influence the connectivity between western and eastern juvenile loggerhead foraging grounds in the North Pacific Ocean.